Thermotropic liquid–crystalline properties of 4, 4′-dialkoxy-3, 3′-diaminobiphenyl compounds and their precursors. Issue 11 (1st September 2016) - Bhowmik, Pradip K.; Killarney, Shane T.; Koh, Jung Jae; Tanthmanatham, Ontida; Han, Haesook; Harris, Tyler; Fisch, Michael R.; Agra-Kooijman, Deña M.; Sharpnack, Lewis; Kumar, Satyendra
ABSTRACT: A series of 4, 4ʹ-dialkoxy-3, 3ʹ-diaminobiphenyl compounds were synthesised by three-step procedure that involves alkylation, nitration and reduction reactions. Their chemical structures were characterised by FTIR, 1 H and 13 C spectroscopy and elemental analysis. Their thermotropic liquid–crystalline (LC) properties were examined by a number of experimental techniques including differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), polarising optical microscopy (POM) and variable temperature X-ray diffraction (VT-XRD). The 4, 4ʹ-dialkoxy-3, 3ʹ-dinitrobipheyl compounds, precursors to the diamine compounds, were also examined for their thermotropic LC properties. POM studies of focal conic textures and VT-XRD of the 3, 3ʹ-diaminobiphenyl derivatives having flexible alkyl chains (C6 –C12 ) exhibited the smectic A (SmA) phase independent of the length of alkyl chains. Similarly, the 3, 3ʹ-dinitrobiphenyl derivatives containing alkyl chains C7, and C9 –C11 exhibit the SmA phase, those containing C8 formed the smectic C (SmC) phase and C12 formed both the SmA and smectic B (SmB) phases, respectively. The 3, 3ʹ-diaminobiphenyl derivatives had excellent thermal stability in the temperature range of 237–329°C, while those of 3, 3ʹ-dinitrobiphenyl derivatives were in the temperature range of 270–321°C. The 3, 3ʹ-diaminobiphenyl derivatives emitted UV light both in chloroform and acetonitrile. Graphical Abstract: